Association between Surface Air Temperature And Land Use On The Campus Scale - Satrio Muhammad Alif; Erwin Yosua; Adam Irwansyah Fauzi; Bambang Edhi Leksono (UIR PRESS, 2020)
The increasing trend of global temperature is related to the land use change in the form of urbanization. The impact of land use change to surface air temperature in Indonesia especially in smaller scope in Indonesia have not researched yet. The study area is located on newly built campus and the development of land use change inside campus can be managed carefully. This research aim is to determine which land use affecting high-temperature by using multiple linear regression method with least square approach so that temperature increase can be controlled in which some land uses must be preserved in urbanization. Land use data is interpreted from the photo map of 275 hectare campus. Temperature data is measured by using the digital thermometer three times a day. The method idea is to obtain distinctive contribution of every land use to every temperature measurement point. The contribution follows the inverse distance weighted concept. Surface air temperature measurement points are located with 150 meter interval and centroids of land use polygons are used for association calculation. Temperature measurement shows values between 25.5oC and 35.4oC. Land use with more anthropogenic activities and rubber plantation are the top contributors to high surface air temperature within a day. In the non-built-up land use category, water body increases the temperature in the daytime. Anthropogenic activities and vegetation density within land use is the main factor in increasing the surface air temperature so that it is suggested to plant farm-like vegetation around every built-up land use.